EVALUATING THE IMPACT OF MAHATMA JYOTIBA PHULE SHETKARI KARJ MUKTI YOJANA ON FARMERS' FINANCIAL STABILITY IN NAGPUR DISTRICT - Tagade, Vigesh Rajkumar; Chaudhari, Tushar V. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kisan Karj Maaf Yojana is the one scheme most affected by the Maharashtra Election – Mahatma Jyotiba Phule Shetkari Karj Mukti Yojana, which is an important agricultural loan waiver scheme of the government, was introduced to alleviate the financial distress faced by the farmers of Maharashtra. Hence this study endeavours to examine the benefits of this scheme to the financial stability of the farmers in Nagpur District. It aims at analysing an overview of debt waiver effectiveness, farmers’ income levels, investment patterns, access to institutional credit of farmers post-waiver. To evaluate the perceptions of beneficiary farmers and financial institutions, a mixed-methods approach was adopted, involving quantitative surveys and qualitative interviews. Evidence suggest that although the initiative has granted temporary relief with fewer debts, the long-term viability and economic merits of this measure are debated and factors such as reduced credit availability, heightened reliance on continued government assistance, and a lack of financial education have been cited as hindrances to the program (Roccasalva, 2019). Overhauling the Loan Waiver Policies in India: The study suggests policy measures to strengthen financial inclusion, promote sustainable farming practices, and ensure better loan repayment mechanisms in order to enhance the effectiveness of loan waiver programmes. By providing analyses of the scheme’s aggregate impact, the research adds empirical evidence to the current debate on how agricultural finance and rural development initiatives can be most effectively implemented.